Effective pollination of greenhouse Galia musk melon (Cucumis melo L. var. reticulatus ser.) by afrotropical stingless bee species. Issue 5 (20th October 2022) - Kiatoko, Nkoba; Pozo, Maria I.; Van Oystaeyen, Annette; van Langevelde, Frank; Wäckers, Felix; Kumar, Raina Suresh; Hundt, Baerbel; Jaramillo, Juliana
Abstract: An increasing demand for pollination services highlights the need for research on alternative pollinators for greenhouse and open field food crops. We compared the foraging behaviour and effectiveness of seven endemic African Meliponinae ( Meliponula bocandei, Dactylurina schmidti, Plebeina hildebrandti, Meliponula lendliana, Hypotrigona gribodoi, Meliponula ferruginea, Meliponula togoensi s) as alternative pollinators to honey bees of greenhouse cultivated Cantaloupe melons. It was observed that honey bees started foraging sooner after introduction in the greenhouse (av. 4 days) than the stingless bee species (8 to 16 days). Stingless bees were mainly harvesting nectar ( ca . 2/3 of all flower visits) and M. ferruginea, M. togoensis, H. gribodoi and P. hildebrandti spent more time collecting nectar than other stingless bee species. Fruit maturation was significantly faster when flowers were pollinated by stingless bees compared to honey bees, with the shortest fruit maturation time found when flowers were pollinated by M. bocandei and H. gribodoi . All treatments resulted in fruits of similar roundness and ellipsoid ratios. The highest fruit weight and fruit volume were obtained from flowers pollinated by either manual pollination, H. gribodoi, M. bocandei, M. lendliana and P. hildebrandti compared to honey bees. Correspondingly, pollination by the latter 5 species resulted in the highest seed counts per fruit, although these differences did not affect seed weight or volume. Altogether, our results indicate that stingless bees such as H. gribodoi, M. bocandei, M. lendliana and P. hildebrandti are more efficient pollinators of sweet melon than A. m. scutellata and can be recommended for use in greenhouse crops.